2016
DOI: 10.17984/adyuebd.87973
|View full text |Cite
|
Sign up to set email alerts
|

Fen Öğretiminde Öğrenilen Kavramların Günlük Yaşamla İlişkilendirilmesi: Su Kimyası ve Su Arıtımı

Abstract: The fulfillment of meaningful learning in the course of teaching process depends upon students' achievement in associating scientific conceptions with the facts they encounter in their daily lives. In science courses, students are generally unable to understand the meanings of the concepts accurately due to the unavailability of using practical examples from daily life in the school settings. In science education, particularly in conceptual learning, the association of the conceptions with daily lives needs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
0
3
0
6
Order By: Relevance
“…In terms of academic success, the average of middle and low level students; in the process of context-based problem solving, they explained the questions based on their own experiences and lives, but they could not establish the relationship between the question and subject. Some previous researches also showed that students cannot associate scientific knowledge with daily life at the desired level (Akgün, Tokur and Duruk, 2016;Ayas, Karamustafaoğlu, Sevim and Karamustafaoğlu, 2001;Baran, Doğan and Yalçın, 2002;Canpolat and Ayyıldız, 2019;Doğan, Kıvrak and Baran, 2004;Emrahoğlu and Mengi, 2012). It can be said that the results of study we conducted is consistent with these studies according to these findings.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of academic success, the average of middle and low level students; in the process of context-based problem solving, they explained the questions based on their own experiences and lives, but they could not establish the relationship between the question and subject. Some previous researches also showed that students cannot associate scientific knowledge with daily life at the desired level (Akgün, Tokur and Duruk, 2016;Ayas, Karamustafaoğlu, Sevim and Karamustafaoğlu, 2001;Baran, Doğan and Yalçın, 2002;Canpolat and Ayyıldız, 2019;Doğan, Kıvrak and Baran, 2004;Emrahoğlu and Mengi, 2012). It can be said that the results of study we conducted is consistent with these studies according to these findings.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Alanyazına baktığımızda öğrencilerin fen bilimleri dersinde öğrendikleri bilimsel bilgileri günlük yaşamdan olaylarla ilişkilendirebilme düzeylerini belirleyebilmek amacıyla bazı araştırmalar yapılmıştır (Akgün, Tokur ve Duruk, 2016;Ayas, Karamustafaoğlu, Sevim ve Karamustafaoğlu, 2001; Balkan, Kıyıcı ve Aydoğdu, 2011; Baran, Doğan ve Yalçın, 2002; Canpolat ve Ayyıldız, 2019; Doğan, Kıvrak ve Baran, 2004;Emrahoğlu ve Mengi, 2012;Gürses ve diğerleri, 2003;Seçken, Yılmaz ve Morgil, 1998;Yiğit, Devecioğlu ve Ayvacı, 2002). Yapılan araştırmalar sonucunda öğrencilerin bilimsel bilgileri günlük yaşamla istenilen düzeyde ilişkilendiremedikleri görülmektedir.…”
Section: Sonuç Tartışma Ve öNerilerunclassified
“…Associating scientific facts with daily life will not only provide meaningful learning (Cajas, 1999), but will also have a positive effect on the student's attitude and motivation. The fact that students can associate the information they have acquired during education with events in daily life is a proof of learning away from rote (Akgün et al, 2016;Canpolat et al, 2019). Therefore, it is important for students to be able to associate the information they have learned during the education process with daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Ülkemizde yapılan çalışmalar okullarda öğretilen kavramların gerçek yaşamla ilişkisinin yeterince ele alınmadığını göstermektedir (Akgün, Tokur ve Duruk, 2016;Balkan-Kıyıcı ve Aydoğdu, 2011;Özay-Köse ve Gül, 2016;Yıldırım, Küçük ve Ayas, 2013). Gerçek yaşamın bir parçası olan fen bilimleri dersinin bile öğrencilerin çevresinde olan olaylara ilgisini ve merakını çekmek konusunda yetersiz kaldığı görülmektedir.…”
Section: Introductionunclassified